1996
DOI: 10.1007/bf02373018
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular proteolytic enzyme activity ofHistoplasma capsulatum var.duboisii

Abstract: Histoplasma capsulatum var. duboisii is the etiological agent of African histoplasmosis, an important deep mycosis in West Africa. Not much is known about the physiological properties of this fungus. This communication reports on the extracellular proteolytic enzyme activity of this fungus. Five isolates of this fungus tested hydrolyzed azocasein and bovine serum albumin at pH 6.8 and 8.0. Assay of the crude enzyme showed that proteolytic activity increased with age and peaked on the 10th day and then again on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
1

Year Published

1997
1997
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 19 publications
(10 reference statements)
0
7
1
Order By: Relevance
“…duboisii and H. capsulatum var. capsulatum (Okeke and Muller, 1991a, Okeke and Muller, 1991b, Muotoe-Okafor et al, 1996. The discrepancies observed between these studies and our work are probably due to differences in methodology, especially in the media tested.…”
Section: Discussioncontrasting
confidence: 75%
See 1 more Smart Citation
“…duboisii and H. capsulatum var. capsulatum (Okeke and Muller, 1991a, Okeke and Muller, 1991b, Muotoe-Okafor et al, 1996. The discrepancies observed between these studies and our work are probably due to differences in methodology, especially in the media tested.…”
Section: Discussioncontrasting
confidence: 75%
“…Dimorphic fungi consist of six phylogenetically related ascomycetes: Blastomyces dermatitidis, Coccidioides immitis, Histoplasma capsulatum, Paracoccidioides brasiliensis, Penicillium marneffei, and Sporothrix schenckii, but only few studies have shown proteolytic activity in vitro (Tsuboi et al, 1986, Sanada, 1987, Tsuboi et al, 1987, Cole et al, 1992, Carmona et al, 1995, Puccia et al, 1998, de Assis et al, 1999, Moon et al, 2006. There are also relatively few reports describing this type of activity in H. capsulatum (Okeke and Muller, 1991a, Okeke and Muller, 1991b, Muotoe-Okafor et al, 1996.…”
Section: Discussionmentioning
confidence: 99%
“…Some of the fungal virulence factors identified to date include proteases, such as the secreted aspartyl proteases from Candida albicans (20,22). Extracellular proteolytic activity has been described previously in H. capsulatum and shown to hydrolyze casein, bovine serum albumin, and collagen (21,23,24,30). However, H. capsulatum protease genes have not been identified.…”
mentioning
confidence: 99%
“…The aspartic protease activity was more pronounced in yeasts than in mycelia [149]. The optimum temperature and pH for maximum proteolytic activity were 35°C and 6.8, respectively.…”
Section: Aspartic Proteasesmentioning
confidence: 89%